a; b; c are three positive reals such that ( a + b + c ) ( a 1 + b 1 + c 1 ) = n and the maximum value of ( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 ) is 1 6 n .
What's the minimum value of ( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We have that ( a + b + c ) ( a 1 + b 1 + c 1 )
= 3 + b a + c a + c b + a b + a c + b c
= 3 + b c c a + b c a b + c a a b + c a b c + a b b c + a b c a
= ( a b + b c + c a ) ( a b 1 + b c 1 + c a 1 ) .
1 6 n + 2 n = ( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 ) + 2 ( a b + b c + c a ) 2 ( a b 1 + b c 1 + c a 1 )
⟺ 6 n ≤ [ a 2 + b 2 + c 2 + 2 ( a b + b c + c a ) ] [ a 2 1 + b 2 1 + c 2 1 + 2 ( a b 1 + b c 1 + c a 1 ) ]
⟺ 6 n ≤ ( a + b + c ) ( a 1 + b 1 + c 1 ) = n
⟺ 6 ≤ n
⟺ 3 6 ≤ n . So the equality happens when n = 3 6 .
(The maximum value of the expression ( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 ) for any n given is n ( n − 2 ) 2 , just to let you know.)
Let x = b a + c b + a c and y = c a + a b + b c
We have that ( a + b + c ) ( a 1 + b 1 + c 1 ) = n
⟺ x + y = n − 3
( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 )
= 3 + b 2 a 2 + c 2 b 2 + a 2 c 2 + c 2 a 2 + a 2 b 2 + b 2 c 2
= 3 + ( b a + c b + a c ) 2 − 2 ( c a + a b + b c ) + ( c a + a b + b c ) 2 − 2 ( b a + c b + a c )
= 3 + x 2 − 2 y + y 2 − 2 x
= 1 + ( 2 x 2 + 2 y 2 − x y ) + ( 2 x 2 + 2 y 2 + x y − 2 x − 2 y + 2 )
= 1 + 2 ( x − y ) 2 + 2 ( x + y − 2 ) 2
≥ 1 + 2 ( x + y − 2 ) 2
= 1 + 2 ( n − 5 ) 2
Plugging in n = 3 6 , we have that ( a 2 + b 2 + c 2 ) ( a 2 1 + b 2 1 + c 2 1 ) ≥ 1 + 2 3 1 2 = 4 8 1 . 5 .